The Relationship Between Dietary Patterns, Nutritional Knowledge, and Early Marriage with the Incidence of Chronic Energy Deficiency Among Pregnant Women in the Working Area of UPTD Puskesmas Barambai - Sumainah; Aprianti; Pratiwi, Niken; Fathurrahman (Jurnal Riset Pangan dan Gizi, 2026)
In Indonesia, Chronic Energy Deficiency (CED) among pregnant women remains a nutritional problem that increases the risk of pregnancy complications, preterm birth, and low birth weight, and contributes to stunting. Data from the working area of UPTD Puskesmas Barambai indicate increasing CED cases, while early marriage is still found in the community. This study aimed to determine the relationship between dietary patterns, nutritional knowledge, and early marriage with the incidence of CED among pregnant women in the working area of UPTD Puskesmas Barambai. A case–control design was used with 48 pregnant women, consisting of 16 cases and 32 controls. Data were collected through interviews using a Food Frequency Questionnaire (FFQ) for dietary patterns, a nutritional knowledge questionnaire, early marriage age data, and Mid-Upper Arm Circumference (MUAC) measurements. Data were analyzed using the Chi-square test with a significance level of α=0.05. The results showed that 33.4% of pregnant women experienced CED, 66.6% had poor dietary patterns, 22.9% had low nutritional knowledge, and 31.3% married early. There were significant relationships between dietary patterns, nutritional knowledge, and early marriage with CED incidence (p<0.05). Pregnant women are expected to improve dietary quality and strengthen nutrition knowledge through education, and early marriage prevention programs should be enhanced to reduce CED incidence.